2019
DOI: 10.1038/s41467-019-11687-8
|View full text |Cite
|
Sign up to set email alerts
|

AAV-ie enables safe and efficient gene transfer to inner ear cells

Abstract: Hearing loss is the most common sensory disorder. While gene therapy has emerged as a promising treatment of inherited diseases like hearing loss, it is dependent on the identification of gene delivery vectors. Adeno-associated virus (AAV) vector-mediated gene therapy has been approved in the US for treating a rare inherited eye disease but no safe and efficient vectors have been identified that can target the diverse types of inner ear cells. Here, we identify an AAV variant, AAV-inner ear (AAV-ie), for gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
139
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 38 publications
4
139
1
Order By: Relevance
“…Viral vectors such as AAV-inner ear, AAV2.7m8, bovine AAV, and adenovirus may be more suitable for selective SC transduction. 9,[19][20][21] It remains unclear why our results appear to diverge from those in prior studies, particularly the observed transduction rates of AAV1 and Anc80 for IHCs and OHCs, respectively, as compared with AAV2. By design, our study leverages a route of administration that differs from routes used in other studies assessing AAV transduction in the cochlea.…”
Section: Discussioncontrasting
confidence: 96%
“…Viral vectors such as AAV-inner ear, AAV2.7m8, bovine AAV, and adenovirus may be more suitable for selective SC transduction. 9,[19][20][21] It remains unclear why our results appear to diverge from those in prior studies, particularly the observed transduction rates of AAV1 and Anc80 for IHCs and OHCs, respectively, as compared with AAV2. By design, our study leverages a route of administration that differs from routes used in other studies assessing AAV transduction in the cochlea.…”
Section: Discussioncontrasting
confidence: 96%
“…The third improvement involves the use of recently reported novel AAVs that have a higher transfection rate. [11][12][13][14]16,69,70 We believe that with these improvements, USMB-mediated cochlear gene transfection via the RWM would become a useful tool that could be translated into human clinical applications.…”
Section: Limitations and Future Improvementsmentioning
confidence: 99%
“…3 This viral vector has been used in the gene therapy studies of auditory system in animal models [11][12][13][14][15] and human trials. 11,16 The inner ear is highly isolated from surrounding organs and tissues. This unique feature makes it an ideal organ for genetic manipulation, with a low risk of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of hearing loss is extremely heterogeneous, and in many regions of the world, deaf people tend to marry with each other to form rather complex deaf families [33][34][35][36][37][38][39][40]. In one such family, we identified two separate genetic causes of hearing loss in distinct affected members, including the recessive c.235delC (p.L79Cfs * 3) mutation in GJB2 (III-2) and the dominant c.481C>T (p.R161C) mutation in SOX10 (II-1, III-1, and IV-1).…”
Section: Discussionmentioning
confidence: 99%